A local church's holistic response to HIV/AIDS - Mboya, Rose (Missionalia: Southern African Journal of Mission Studies, 2010)
This paper is an attempt to contribute to demonstrating ways in which a local church can respond to HIV/AIDS in a holistic way. The main argument in this paper is that in order for churches to respond holistically, engaging in re-structuring society's viewpoint so that men and women can relate in a healthy manner, as opposed to the manner in which they relate today, is a necessity. Also, that it is crucially important for churches to address all aspects that affect life and to reconsider the meaning of terms such as marriage and love in the context of HIV/AIDS.
Paid